Development of a river basin monitoring system for Malaysia - Bopi, Nor Bazilah; Ismail, Ahmad Fadzil; A. Zabidi, Suriza; Hasan, Mohammad Kamrul (NADIA, 2016)
Floods are one of the major disasters occurring all over the world, including Malaysia. It can lead to the destruction of facilities, infrastructures as well as properties. Minimizing the risk of hazards and loss can be achieved by implementing several measures. Motivated by one of the biggest flood disasters ever occurred in the country, this monitoring system is developed as a means to reduce the risk of loss and damages. Monitoring rainfall rates may assist the community as it can provide early flood forecasting even though it cannot fully prevent the flood. Besides, it can give additional information on the probability of landslide occurrences. This paper presents the development of a useful and reliable rainfall rate monitoring system for online hydrological stations in Kelantan. The whole process in the development of this first prototype are conducted and performed using open-source software and tools such as Visual Basic and Quantum GIS (QGIS).